Development of MOF "Armor‐Plated" Phycocyanin and Synergistic Inhibition of Cellular Respiration for Hypoxic Photodynamic Therapy in Patient‐Derived Xenograft Models. Issue 3 (4th December 2020) - Chen, Danyang; Suo, Meng; Guo, Jiancheng; Tang, Wenxue; Jiang, Wei; Liu, Ying; Duo, Yanhong
Abstract: Significant progress has been made in the use of phycocyanin (PC) as a photosensitizer (PS) agent for photodynamic therapy (PDT). The clinical use of PC, however, has been limited by its poor stability, unfavorable pharmacokinetics, limited tumor cell uptake, and the hypoxic nature of the tumor microenvironment. In this study, a novel biomimetic mineralization approach is described for encapsulating PC using zeolitic imidazolate framework‐8 (ZIF‐8), after which MPEG2000 ‐COOH is further utilized as an anchor on the ZIF/PC complex in order to yield MPEG2000 ‐ZIF/PC composites (PMs). These PMs are then used as a stable reinforced PS for PDT, effectively improving the intracellular delivery of this protein PS. In contrast to prior studies that have sought to overcome intratumoral hypoxia via increasing oxygen delivery to the tumor site, the mitochondrial complex I inhibitor papaverine (PPV) is instead utilized to reduce intratumor oxygen consumption in an effort to augment the PDT efficacy of the PMs. It is found that this combination treatment strategy markedly improves the antitumor properties of these PMs both in vitro and in patient‐derived xenograft (PDX) models without inducing significant side effects. It is therefore proposed that the "armor‐plating" of protein PS agents with ZIF‐8 in combination with PPV may be a promising approach to precision medicine‐mediated tumor treatment. Abstract : Herein, a combined treatment strategy is developed by utilizing a mitochondrial complex I inhibitor to concurrently reduce intratumoral oxygen demands with the goal of enhancing the anticancer activity of zeolitic imidazolate framework‐8 (ZIF‐8) "armor‐plated" phycocyanin, and in vitro and in patient‐derived xenograft (PDX) models results reveal markedly improved antitumor ability without inducing significant side effects.